2011
DOI: 10.1111/j.1551-2916.2011.04833.x
|View full text |Cite
|
Sign up to set email alerts
|

Sintering Effect on Microstructure and Properties of (K,Na)NbO3 Ceramics

Abstract: (K,Na)NbO3 (KNN) lead‐free ceramics were fabricated using conventional solid‐state reaction method. The domain configurations were studied with transmission electron microscopy and found to be closely related to the sintering temperature and cooling rate. High density ceramics with uniform compositions were obtained when sintered at 1200°C with a slow cooling rate, resulting in the improved piezoelectric properties, with d33 on the order of 150–160 pC/N, which is comparable to the hot pressed KNN ceramics. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
62
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 45 publications
(63 reference statements)
10
62
0
2
Order By: Relevance
“…It was suggested that producing a transient liquid phase promoted inter-diffusion and improved chemical homogeneity. Zhang and co-workers 25) investigated cooling effect on the microstructure of KNN samples sintered in the solid+liquid region (sintered at 11701200°C) of the phase diagram for x = 0.5 composition. Na and K inhomogeneity was mostly reported in quenched samples.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that producing a transient liquid phase promoted inter-diffusion and improved chemical homogeneity. Zhang and co-workers 25) investigated cooling effect on the microstructure of KNN samples sintered in the solid+liquid region (sintered at 11701200°C) of the phase diagram for x = 0.5 composition. Na and K inhomogeneity was mostly reported in quenched samples.…”
Section: Discussionmentioning
confidence: 99%
“…The K/Na ratio in the liquid phase is also different from the nominal stoichiometry due the higher melting point of NaNbO3, and a inhomogeneous distribution of K and Na in the sintered materials is expected as previously observed by several groups. 11,55,57 If large amounts of liquid phase are formed, more rearrangement can occur, and the secondary phase segregates into clusters during normal cooling rates (Fig. 11(c) and (d)).…”
Section: Koh (Ls) = 2 K (G) + H2o (G) + ½ O2 (G)mentioning
confidence: 99%
“…All these factors have detrimental effect on the piezoelectric properties of KNN. Though, it is important to mention here that in a more recent study, KNN ceramic sintered at 1,200°C for elongated period has been reported to have high density with improved longitudinal piezoresponse [17].…”
Section: Introductionmentioning
confidence: 97%
“…Most common of them is the use of different oxides as sintering additives which melt below the sintering temperature of KNN and provide higher density by means of liquid phase sintering (LPS) [6,15,18] (KCN) and MnO 2 are few of the most common sintering additives used with KNN [6,[13][14][15][16][17][18][19][20]. But, during sintering, most of these additives diffuse in the KNN lattice and alter the stoichiometry [6,13,14,16].…”
Section: Introductionmentioning
confidence: 99%